Empirical analysis with decentralized finance - Truong, Cong Cuong (Nanyang Technological University, 2022)
Decentralized finance (DeFi) is a new suite of finance services based on blockchain that are trustless, non-custodial, permissionless and transparent. At the end of March 2022, the whole industry was reported by DefiLlama to secure more than 200 USD billion in assets. One of DeFi main innovations is composability, which is the ability of new protocols leveraging the existing ones to unlock new use cases. This study collected addresses of 30 DeFi protocols from Polygon PoS, a side chain helping scale Ethereum network. By using Google BigQuery to collect on-chain data, the author analyzed the network comprising direct interactions between these protocols addresses and extracted building blocks from traces generated by transactions to the addresses. The result shows that the network of direct interaction is sparse, has low assortativity and there is interconnectedness between DeFi protocols. Besides, the building blocks extraction unveils the top 10 frequent building blocks in Polygon ecosystem, demonstrates the composability of DeFi and shows the importance of Quickswap and Aave within Polygon DeFi ecosystem.